Small bowel leiomyosarcoma: previous communication - González Fernández, Alides; Mendivil Herrera, Javier (Cirugía del Uruguay, 1972)
These two cases of leiomiosarcoma of the small intestine have in common, not only their Pathological Anatomy, but also similar clinical apppearence. Their clinical characteristics are discussed and their complete anatomo-pathological reports are transcribed. The general guidelines of the treatment are discussed and both national and foreign case material is revised.